Qualitative Analysis of Medical Record Documents in Inpatient Patients in the Public Health Center - Sri Wahyuningsih Nugraheni; Satinder Kumar; Laila Rizky Azizah (Global Health Science Group, 2023)
The community health center is one of the first level health service facilities that is required to maintain medical records. Medical record is a document that contains patient identity data, examinations, treatment, actions, and other services that have been given to patients. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning medical records, Article 18 states that medical records are analyzed quantitatively and qualitatively. Qualitative analysis aims to ensure complete and accurate medical record data. Objective: The research objective was to determine the completeness and consistency of medical records based on six reviews. Method: This type of research is descriptive research with a retrospective approach. The population is 432 inpatient medical record documents, sample 81 inpatient medical record documents using simple random sampling technique. Collecting data using interviews and observation. Data processing, data presentation and data analysis were carried out on quantitative data and qualitative data in a non-statistical or descriptive manner in tabular and textular forms. Results: The results of the study: 1) review of the completeness and consistency of diagnosis by 71 (88%), 2) review of the consistency of recording diagnoses by 80 (99%), 3) review of things done during care and treatment by 81 (100%), 4 ) review of 8 forms of informed consent by 8 (100%), 5) review of recording techniques by 71 (88%), and 6) review of potential compensation matters by 66 (81%). Conclusions: The results of a qualitative analysis of medical record documents based on the six highest reviews were on the review of recording things that were done during care and treatment as well as the review of complete informed consent, namely 81 (100%), while the lowest review was on the review of things that had the potential for compensation, namely 66 (81 %). The researcher's suggestion to improve the completeness and consistency is to increase the commitment of Caring Professionals (doctors, midwives, nurses, medical recorders) regarding the importance of the completeness and consistency of medical records and the implementation of comprehensive and continuous quantitative and qualitative analyzes.